A Non-redundant Function of MNS5: A Class I α-1, 2 Mannosidase, in the Regulation of Endoplasmic Reticulum-Associated Degradation of Misfolded Glycoproteins - Sun, Xiaoxia; Guo, Chenchen; Ali, Khawar; Zheng, Qian; Wei, Qiang; Zhu, Yumeng; Wang, Li; Li, Guishuang; Li, Wenjuan; Zheng, Bowen; Bai, Qunwei; Wu, Guang (Frontiers in Plant Science, 2022)
Endoplasmic Reticulum-Associated Degradation (ERAD) is one of the major processes in maintaining protein homeostasis. Class I α-mannosidases MNS4 and MNS5 are involved in the degradation of misfolded variants of the heavily glycosylated proteins, playing an important role for glycan-dependent ERAD in planta. MNS4 and MNS5 reportedly have a functional redundancy, meaning that only the loss of both MNS4 and MNS5 shows phenotypes. However, MNS4 is a membrane-associated protein while MNS5 is soluble protein, and both can localize to the endoplasmic reticulum (ER). Furthermore, MNS4 and MNS5 differentially demannosylate the glycoprotein substrates. Importantly, we found that their gene expression patterns are complemented rather than overlapped. This raises a question whether they indeed work redundantly, warranting a further investigation. Here, we conducted an exhaustive genetic screen for a suppressor of the bri1-5, a brassinosteroid (BR) receptor mutant with its receptor downregulated by ERAD, and isolated sbi3, a suppressor of bri1-5 mutant named after sbi1 (suppressor of bri1). After genetic mapping together with the whole genome re-sequencing, we identified a point mutation G343E in AT1G27520 (MNS5) in sbi3. Genetic complementation experiments confirmed that sbi3 was a loss-of-function allele of MNS5. In addition, sbi3 suppressed the dwarf phenotype of bri1-235 in proteasome-independent ERAD pathway and bri1-9 in proteasome-dependent ERAD pathway. Importantly, sbi3 could only affect BRI1/bri1 with kinase activities such that it restored BR-sensitivities of bri1-5, bri1-9 and bri1-235 but not null bri1. Furthermore, sbi3 was less tolerant to tunicamycin and salt than wild type plants. Thus, our study uncovers a non-redundant function of MNS5 in the regulation of ERAD as well as plant growth and ER stress response, highlighting a need of the traditional forward genetic approach to complement the T-DNA or CRISPR-Cas9 systems on gene functional study.